The Effect Of Organizational Culture And Procedural Justice On Organizational Citizenship Behavior - Khulil Fathuroni (Eduvest - Journal of Universal Studies, 2021)
This study aims to show the influence of Organizational Culture and Procedural Justice on Organizational Citizenship Behavior (Study on IT Companies In Special Region of Yogyakarta) which is focused on the high low organizational culture of a company. Samples in this study as many as 9 IT companies with convenience sampling method. The population in this study is all IT companies in Isitimewa Area of Yogyakarta. The data type in this study is primary data. The data source in this study is the results of surveys, interviews and filling out questionnaires from employees of IT companies in the Special Region of Yogyakarta who became research samples. The results of this study show that organizational culture and procedural justice have a significant effect on organizational citizenship behavior in IT companies in Dareah Istimewa Yogyakarta. But for companies whose organizational culture is low organizational culture has no effect on organizational citizenship behavior in IT companies in the Special Region of Yogyakarta.